2016
DOI: 10.1371/journal.pone.0146959
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of a Polygalacturonase-Inhibiting Protein from Cynanchum komarovii That Confers Fungal Resistance in Arabidopsis

Abstract: Compliance with ethical standards: This study did not involve human participants and animals, and the plant of interest is not an endangered species.Polygalacturonase-inhibiting proteins (PGIPs) are leucine-rich repeat proteins that plants produce against polygalacturonase, a key virulence agent in pathogens. In this paper, we cloned and purified CkPGIP1, a gene product from Cynanchum komarovii that effectively inhibits polygalacturonases from Botrytis cinerea and Rhizoctonia solani. We found the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…This provides indirect evidence that PGs are important pathogenic factors in the infection of Arabidopsis by the two fungal pathogens. Previous studies have reported the effectiveness of PGIP in reducing the disease symptoms in other transgenic plants infected with B. cinerea and Cercospora nicotianae 1841. Here, we provide evidence that GhPGIP1 gene can also protect Arabidopsis against infection by the two fungi.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…This provides indirect evidence that PGs are important pathogenic factors in the infection of Arabidopsis by the two fungal pathogens. Previous studies have reported the effectiveness of PGIP in reducing the disease symptoms in other transgenic plants infected with B. cinerea and Cercospora nicotianae 1841. Here, we provide evidence that GhPGIP1 gene can also protect Arabidopsis against infection by the two fungi.…”
Section: Discussionsupporting
confidence: 64%
“…Firstly, top 20 solutions of the complexes were generated by PatchDock, according to the scoring function used. Subsequently, FireDock was used for the fast interaction refinement of the top 10 complexes that were rescored according to the criteria described previously41. Then the prediction candidate models were re-ranked due to re-refinement and optimization (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations